Sharing Electronic Resources Among Three Institutions - Sayed, Ellen; Burnett, Alice (Qualitative and Quantitative Methods in Libraries; Vol 3 No 1 (2014): March 2014 Issue, 2017)
This paper discusses the co-operation between Cornell University in Ithaca, New York, Weill Cornell Medical College in New York, and Weill Cornell Medical College in Qatar. The University in Ithaca was founded 147 years ago in 1865, the College in New York began in 1898, 114 years ago, and the College in Qatar was established in January 2001 in a partnership between Cornell University and Qatar Foundation. Co-operation and communication between the three partners is essential to make the partnership work successfully. The actions, procedures, and problems encountered along the way are presented, along with metrics for the collection in Doha.